Endothelial dysfunction and arterial stiffness in patients with systemic lupus erythematosus: A systematic review and meta-analysis (2020)
Background and aims: Non-invasive surrogates of cardiovascular (CV) disease such as endothelial dysfunction (ED) and peripheral arterial stiffness (AS) have been evaluated in systemic lupus erythematosus (SLE) patients. The aim of this study was to systematically review and meta-analyze reports of cardiovascular disease (CVD) in SLE patients, as measured by ED and AS. Methods: Studies analyzing the relationship of SLE with ED (flow-mediated dilatation [FMD], nitroglycerin-mediated dilatation [NMD] and peripheral arterial tonometry [PAT]) and AS (augmentation index [AIx], pulse wave velocity [PWV]) were systematically searched for in PubMed, Cochrane library, EMBASE, VHL, SciELO and Web of Science databases. Inclusion criteria included peer-review and English language. Mean differences (MD) and 95% confidence intervals (CIs) were estimated using the random effect model. The study was registered with PROSPERO, number CRD42019121068. Results: The meta-analysis included 49 studies. FMD data from 18 studies including 943 SLE subjects (mean age = 38.71 [95%CI 36.21, 41.21] years) and 644 unaffected controls (mean age = 38.63 [95%CI 36.11, 41.15] years) were included. When compared with unaffected controls, FMD in SLE subjects was decreased by 4.3% (95%CI: ?6.13%, ?2.47%): p less than 0.001). However, NMD did not significantly differ between SLE patients and controls (MD = ? 2.68%; 95% CI -6.00, 0.62; p = 0.11). A significantly increased AS between SLE patients and controls according to overall PWV (MD = 1.12 m/s; 95% CI 0.72–1.52; p less than 0.001) was observed, but not for the brachial-ankle PWV. AIx was also increased in SLE patients compared with healthy controls (MD = 4.55%; 95% CI 1.48–7.63; p = 0.003). Conclusions: Overall, SLE patients showed impaired FMD, an independent predictor of CV events. There was a higher degree of AS in SLE patients compared with controls. ED and AS in SLE should be considered when planning preventive strategies and therapies. © 2020 Elsevier B.V.